Seroprevalence and Risk Factors Associated with Hepatitis B Virus Infection among Pregnant Women Attending Antenatal Care in Azare, Bauchi State, Nigeria - Umar H, A.; Aisha, H.Z.; Hussaini, I.H.; Aliyu, M.S. (UMYU Journal of Microbiology Research)
Hepatitis B virus is known to thrive in peripheral mononuclear cells, tissues of pancreas, spleen, kidney, skin, fluids such as saliva, semen, sweat, breast milk, tears, urine as well as vaginal secretion. This study was carried out to determine the seroprevalence of Hepatitis B virus infection and associated risk factors among pregnant women attending antenatal care in General Hospital Azare, Bauchi State. In this study, 100 consenting pregnant women were recruited and their blood samples were screened for HBs Ag using Rapid Test Strip. A structured questionnaire was used to obtain information about the socio-demographic and risk factors of the study population. Data obtained were subjected to Chi-square test using statistical package for social science (SPSS) version 20 to determine the association between risk factors and Hepatitis B virus infection. The result showed that the overall seroprevalence of Hepatitis B virus infection among pregnant women attending General Hospital, Azare, was 6(6.0%). Highest seroprevalence of HBsAg (16.7%) was observed among pregnant women within the age group of 36-40 years so also unemployed pregnant women (6.8%) had the highest seroprevalence of HBs Ag. Previous history of blood transfusion, previous history surgery, use  of contraceptives, sharing of sharp objects and sharing of tooth brush were found to be the risk factors associated with pregnant women in Azare. The differences observed in the seroprevalence of HBs Ag with different demographic and risk factors were not significant (P>0.005), with the exception of age (p = 0.03). Pregnant women and the general public should be enlightened on the risk factors associated with hepatitis B virus infection.